Care recommendations for the respiratory complications of esophageal atresia‐tracheoesophageal fistula. Issue 10 (7th August 2020) - Koumbourlis, Anastassios C.; Belessis, Yvonne; Cataletto, Mary; Cutrera, Renato; DeBoer, Emily; Kazachkov, Mikhail; Laberge, Sophie; Popler, Jonathan; Porcaro, Federica; Kovesi, Thomas
Abstract: Tracheoesophageal fistula (TEF) with esophageal atresia (EA) is a common congenital anomaly that is associated with significant respiratory morbidity throughout life. The objective of this document is to provide a framework for the diagnosis and management of the respiratory complications that are associated with the condition. As there are no randomized controlled studies on the subject, a group of experts used a modification of the Rand Appropriateness Method to describe the various aspects of the condition in terms of their relative importance, and to rate the available diagnostic methods and therapeutic interventions on the basis of their appropriateness and necessity. Specific recommendations were formulated and reported as Level A, B, and C based on whether they were based on "strong", "moderate" or "weak" agreement. The tracheomalacia that exists in the site of the fistula was considered the main abnormality that predisposes to all other respiratory complications due to airway collapse and impaired clearance of secretions. Aspiration due to impaired airway protection reflexes is the main underlying contributing mechanism. Flexible bronchoscopy is the main diagnostic modality, aided by imaging modalities, especially CT scans of the chest. Noninvasive positive airway pressure support, surgical techniques such as tracheopexy and rarely tracheostomy are required for the management of severe tracheomalacia. Regular long‐term follow‐up by a multidisciplinary team was considered imperative. Specific templates outlining the elements of the clinical respiratory evaluation according to the patients' age were also developed.